Efektivitas Penerapan Rehabilitasi dalam Tindak Pidana Penyalahgunaan Narkotika di Tingkat BNN Kota Surabaya Studi Kasus: Klien yang Pernah Menjalani Rehabilitasi 3 Kali - Heru Prasetyo; Cykha Prameswari Kusumaningrum; Natasya Dwi Septiana Aji; Febri Dwi Safitri; Nadia Mutiara Hasri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the effectiveness of the implementation of rehabilitation in narcotics abuse criminal cases at the National Narcotics Agency (BNN) of Surabaya, focusing on a case study of a client who has undergone rehabilitation three times (Case Number R/56/I/KA/PB.06.01/2026/BNNK SBY). This research applies an empirical juridical approach with sociological, juridical, and case study methods to examine the gap between legal norms and their implementation in practice. The findings show that, normatively, Indonesia has established a comprehensive legal framework through the Narcotics Law, the National Criminal Code, Government Regulations, BNN Regulations, Presidential Regulations, and Supreme Court Circulars, all of which emphasize a rehabilitative and restorative justice approach. However, in practice, rehabilitation at BNN Surabaya has not been effective due to limited service capacity, shortage of professional staff, and the lack of an integrated post-rehabilitation monitoring system. The case study reveals repeated relapse caused by weak follow-up supervision and insufficient social support systems. In addition, the incomplete fulfillment of the state’s constitutional responsibility under Article 34 of the 1945 Constitution and the absence of a structured post-rehabilitation system contribute to high recidivism rates. Therefore, drug rehabilitation in BNN Surabaya remains largely formalistic and has not yet functioned effectively as a sustainable social recovery mechanism.